1. Rozwiąż równania
a) -5x + 10 = -2x – 8
b) 7x + 14 = 5x – 22
c) -3 + 2x – 6 = 3 – 4x
d) -5x + 12 + x = 2x – 12
e) 2(x – 3) + 3(4 – x) = 5
f) 2(x + 4) – 5(x + 3) = 2
g) 3(x – 4) – 2(2x – 5) = -4
h) -2(x + 3) + 4(2x + 3) = -6


Odpowiedź :

Odpowiedź:

a)

-5x+2x=-10-8

-3x=-18 |:3

x=-6

b)

7x-5x=-14-22

2x=-36 |:2

x=-18

c)

4x+2x=3+6+3

6x=12 |:6

x=2

d)

-5x+x-2x=-12-12

-6x=24 |:6

x=4

e)

2x+6+12-3x=5

2x-3x=5-6-12

x=-23

f)

2x+8-5x-15=2

2x-5x=2+15-8

-3x=9 |:3

x=3

g)

3x-12-4x+10=-4

3x-4x=-4+12-10

x=-2

h)

-2x-6+8x+12=-6

-2x+8x=-12

6x=-12 |:6

x=-2